2014
DOI: 10.1016/j.rehab.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual disorders in men with multiple sclerosis: Evaluation and management

Abstract: Sexual dysfunction (SD) is a common feature of men with multiple sclerosis. SD is often unrecognized as patients and physicians are reluctant to discuss these problems. Rates of symptoms range from 50% to 90% and include erectile dysfunction, ejaculatory dysfunction, orgasmic dysfunction and reduced libido. SD can arise at any stage of the disease, even without severe disability. While erectile dysfunction is thought to be related to impairment of the pathways in the spinal cord, fatigue, spasticity, bladder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Psychosocial factors are of great importance in the evaluation of depression and SD in MS patients. A major limiting factor is that studies evaluating the impact of these factors are cross sectional, lacking follow up data [10][11][12] . Results of these studies have shown that the most important problem in the evaluation and treatment of MS patients with depression and SD is focus on emotion/state rather than the problem that has caused it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial factors are of great importance in the evaluation of depression and SD in MS patients. A major limiting factor is that studies evaluating the impact of these factors are cross sectional, lacking follow up data [10][11][12] . Results of these studies have shown that the most important problem in the evaluation and treatment of MS patients with depression and SD is focus on emotion/state rather than the problem that has caused it.…”
Section: Discussionmentioning
confidence: 99%
“…Both SD and depression are very often under-recognized, but have considerable impact on the patient quality of life. Th erefore, in the evaluation of patients with MS, it is of great importance to pay attention not only to functional defi cit, but also to mood changes, SD and quality of life [6][7][8][9][10][11] . Due to the complexity and multifactorial nature of SD and its clinical manifestations, multidisciplinary approach is of great importance in MS patients, including neurologist, physical therapist, psychiatrist, urologist and educated nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of SD in MS patients is complex and its cause is debatable [3,11]. There seems to be a complex interaction among social, physiological and psychological factors that is strongly affected by emotions and social elements [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunctions in patients with MS are often divided into primary—caused by direct demyelination in regions affecting sexual response, resulting in inability to achieve orgasm, difficulties with arousal or genital sensation, secondary—caused by physical signs associated with sexual response, such as increased fatigue, pain due to inadequate lubrication, motor deficit or muscle spasticity, and tertiary—caused by psychological and sociological impairment, which often leads to lower self‐esteem and depression which have a negative effect on sexuality (Previnaire, Lecourt, Soler, & Denys, ).…”
Section: Introductionmentioning
confidence: 99%